STRONG INBREEDING DEPRESSION IN TWO SCANDINAVIAN POPULATIONS OF THE SELF‐INCOMPATIBLE PERENNIAL HERB ARABIDOPSIS LYRATA. (24th June 2013) - Sletvold, Nina; Mousset, Mathilde; Hagenblad, Jenny; Hansson, Bengt; Ågren, Jon
<x xml:space="preserve">Abstract</x> Inbreeding depression is a key factor influencing mating system evolution in plants, but current understanding of its relationship with selfing rate is limited by a sampling bias with few estimates for self‐incompatible species. We quantified inbreeding depression (δ) over two growing seasons in two populations of the self‐incompatible perennial herb Arabidopsis lyrata ssp. petraea in Scandinavia. Inbreeding depression was strong and of similar magnitude in both populations. Inbreeding depression for overall fitness across two seasons (the product of number of seeds, offspring viability, and offspring biomass) was 81% and 78% in the two populations. Chlorophyll deficiency accounted for 81% of seedling mortality in the selfing treatment, and was not observed among offspring resulting from outcrossing. The strong reduction in both early viability and late quantitative traits suggests that inbreeding depression is due to deleterious alleles of both large and small effect, and that both populations experience strong selection against the loss of self‐incompatibility. A review of available estimates suggested that inbreeding depression tends to be stronger in self‐incompatible than in self‐compatible highly outcrossing species, implying that undersampling of self‐incompatible taxa may bias estimates of the relationship between mating system and inbreeding depression.